Indonesia Economic Quarterly, September 2009 : Clearing Skies - World Bank (World Bank, Washington, DC, 2018)
In the first half of 2009, Indonesia's economy has established a solid recovery from late last year. Quarterly growth has accelerated since the start of 2009, after stalling in the final quarter of 2008, although the year-on-year growth rate has continued to slow, recording 4.0 per cent in the year to Q2. This trend of a gradual recovery is projected to continue into 2011. Indonesia's recovery coincides with an improved external environment. Q2 gross domestic product (GDP) outcomes across its major export destinations were better than expected and most trading partner's exited recession by mid-year. International prices of many of Indonesia's exports have recovered much of their late 2008 falls. These developments have supported Indonesia's economy, with exports recovering faster than imports. Domestic consumption continued to contribute strongly to growth in the second quarter. In the first quarter, large amounts of spending by campaign teams for the parliamentary election lifted private consumption. Indonesia's financial markets have continued to strengthen through Q2, generally by more than markets elsewhere in the region. The rupiah has continued to appreciate against the weakening USD, although at a slowing rate, and stabilized around 10,000 per USD by early September. The stock market also performed strongly in Q2, rising over 20 per cent from late May to early September. By mid-June, yields on sovereign rupiah bonds had returned to early 2008 levels, while the spread on Indonesian government USD bonds had the global emerging market average. From late June to September, local currency bond yields have remained broadly stable, while spreads on USD bonds have fallen another percentage point. These improved market conditions have allowed the government to continue financing its budget through the bond market, accessing funds for longer terms and at lower yields.